Krajowy system ratowniczo-gaśniczy w zarządzaniu kryzysowym - Czudiak, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article characterizes the essence of cooperation and dependence between the National rescue and fire extinguishing system and the crisis management system. The study indicates the origin of the indicated systems, the legal basis for their functioning, and the administration bodies performing the tasks. The purpose of the publication is to describe the structure of the rescue and firefighting system and crisis management together with the presentation of their common elements. The author describes, amongst other features, the operating phases of individual systems, taking into account convergent and corresponding elements. The postulates that the systems complement each other, and the primary objective of their functioning is to act for the benefit of citizens’ and state security.
Keywords: bezpieczeństwo państwa; bezpieczeństwo wewnętrzne; zarządzanie kryzysowe; system ratowniczy; administracja publiczna; wojewoda; starosta